The Implementation of Blended Learning in Teaching Reading Comprehension at the Senior High School - Wiki Harianti; Rengganis Siwi Amumpuni; Arri Kurniawan (Applied Research on English Education (AREE), 2023)
Reading is an important activity for obtaining information. This research tries to investigate the use of blended learning in teaching reading, and the purpose is to describe: the implementation of Blended Learning in teaching reading comprehension, the outcome of using Blended Learning in teaching reading toward the student’s mastery of reading, and the advantages and disadvantages of Blended Learning in teaching reading comprehension. This research employed a qualitative research approach to describe data. This research used a descriptive qualitative type of research. The data collection was done by using observation, interviews, and documentation. The source of data were social situations, participants, and documents, and to take the data uses, purposive sampling. The sample is XC. In addition, the steps of analysis in research are data reduction, data display, and conclusion and verification. The result of this research is there are three procedures of using blended learning: pre-activity, whilst activity, and post-activity. The outcome of implementing blended learning is the student’s achievement better. The advantages are: the students can access the internet to get more information, are more accessible to answer the exercise and translate the reading, be more accessible r to understand the text, and it is more practical and effective. The disadvantages are the internet signal, power outages, the ability to operate the computer application, facility of the computer itself. In addition, there is a suggestion for future research. The researcher invites the other researchers to do another study on blended learning.Keywords: teaching; reading; blended learning